UPAYA PEMBINA DALAM MENINGKATKAN PARTISIPASI AKTIF HIDUP MENGGEREJA ORANG MUDA KATOLIK DI PAROKI ST. YOHANES PAULUS II NAMO PECAWIR-TUNTUNGAN - Tibo, Paulinus; Sembiring, Joy Kansius; Bere, Paulus Halek (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2024)
This research examines the efforts of coaches to increase active participation in OMK church life at the Namo Pecawir Paroki St. John Paul II Namo Pecawir-Tuntungan station. The purpose of this study was to find out the efforts of coaches to increase the active participation of young Catholics in church life. This type of research is qualitative research. Data collection techniques are observation, interviews and documentation. Informants are divided into three parts, namely key informants, main informants and additional informants. The number of informants in this study amounted to 6 people, of which 1 coach, 1 coordinator, 1 church administrator and 3 young Catholics. The result is that the coach's efforts to increase active participation in OMK church life have been carried out and are running well. The efforts of OMK coaches and church life have been good, but in practice it should be further improved and developed again in various activities. Especially in mutual cooperation activities, environmental prayer, liturgical officers, and deepening of faith. The presence of OMK must be further enhanced to support the development of church life. The coach's efforts in providing direction, accompanying, and becoming a friend for OMK are further enhanced so that they have a good influence on the development of OMK.